2020
DOI: 10.1080/23802359.2020.1731350
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the giant panda tick Haemaphysalis flava (Acari, Ixodidae) from Southwest China

Abstract: The tick Haemaphysalis flava (Acari, Ixodidae) is an obligatory blood-feeding ectoparasite of the giant panda and is also a vector for transmission of pathogenic microorganisms. In this study, the complete mitochondrial genome of this tick was sequenced through Illumina sequencing technology. The genome was 14,699 bp in length and encoded 37 genes including 13 protein-coding genes, 22 transfer RNAs and two ribosomal RNAs. Phylogeny revealed that three isolates of H. flava, regardless of host origins and locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…ava and Ha. longicornis species (99.11% and 100% identity, respectively) identi ed in this work is similar to that reported in previous studies [32][33][34][35]. However, the single species of Ha.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…ava and Ha. longicornis species (99.11% and 100% identity, respectively) identi ed in this work is similar to that reported in previous studies [32][33][34][35]. However, the single species of Ha.…”
Section: Discussionsupporting
confidence: 89%
“…Haemaphysalis ava has a broad geographic distribution in Asia [2]. It was mainly distributed in Hubei Province [32], Hunan Province, and Southwest China [33]. Previous studies reported that Rhipicephalus sanguineus and Ha.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome (mitogenome) is a reliable marker for cryptic species identification, phylogenetic studies, and population genetics analysis, and has been widely used in animals [ 23 , 24 , 25 , 26 , 27 , 28 ], including in ticks [ 7 , 21 , 29 ]. In recent years, the number of sequenced mitogenomes of Ixodidae species has increased significantly, but the mitogenome studies on parasitic ticks of giant pandas have only been performed for three Haemaphysalis species [ 30 , 31 , 32 ]. The mitogenomes of another ten Ixodidae species infesting giant pandas have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The gene arrangement was identical to soft ticks and non-Australasian Ixodes species (Chen et al 2020). Four of these PCGs (NAD4, NAD4L, NAD1 and NAD5) were located on the light strand (L-strand), all other remaining PCGs were anchored on the heavy strand (H-strand) (Wang et al 2020). We observed that the size of 22 transfer RNA genes ranging from 56 bp (tRNA-Ser) to 68 bp (tRNA-Lys), nine tRNA genes (tRNA-Gln, tRNA-Cys, tRNA-Tyr, tRNA-Phe, tRNA-His, tRNA-Pro, tRNA-Leu1, tRNA-Leu2, tRNA-Val) were encoded on the L-strand.…”
mentioning
confidence: 92%